Mental health impact by COVID-19 in hospitalized patients sample in Mexico City - Maya Piña, Lucía-Verónica; Barbosa-Cobos, Rosa-Elda; Lugo-Zamudio, Gustavo-Esteban; Chacón-Abril, Karla-Lorena; Padrón-Ramírez, Mayela; Jiménez-Jiménez, Xóchitl; Vuelvas-Olmos, César-Rubén; Cortés-Álvarez, Nadia Yanet; Jiménez Jiménez, Saúl (Anales de Psicología / Annals of Psychology, 2022)
One of the consequences of pandemic is the increase in the prevalence of mental alterations such as anxiety, depression and stress. Since here, we aimed to determinate through a transversal and observational study prevalence of stress, anxiety and depression within hospitalized patients by COVID-19 as well as their likely association with the emotional impact received by relatives with hospitalized patients by COVID-19. Forty-five COVID-19 hospitalized patients with mean age of 54.4 ± 9.6 years and fifty-five relatives with mean age of 43.2 ± 11.8 years answered a questions battery and DASS-21 survey. Our results revealed high prevalence of depression, anxiety and stress assessed by DASS-21 subscales. We also identified risk factors associated with the emotional health such as age (< 50 years: depression OR = 2.99 [1.31, 6.80], p < .05 and anxiety OR = 2.83 [1.15, 6.93], p < .05), by gender (female: anxiety OR = 4.13 [1.57, 10.89], p < .05 and stress OR = 5.38 [2.27, 12.8], p < .05), by group of study (relatives: depression OR = 3.83 [1.63, 8.96]; p < .05, anxiety OR = 3.60 [1.46, 8.88]; p < .05 and stress OR = 3.30 [1.41, 7.70]; p < .05). Additionally, female gender and low socioeconomic status in patients (β = 3.23; 1.96) and relatives (β = 1.86; 2.31) were associated with higher scores in anxiety (p < .05) and stress (p < .05). We concluded that our sample of COVID-19 patients maintain a high prevalence of mental alterations and age, gender and socioeconomic status modify the magnitude of these disorders.